10-6f=-10-10f

Simple and best practice solution for 10-6f=-10-10f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-6f=-10-10f equation:



10-6f=-10-10f
We move all terms to the left:
10-6f-(-10-10f)=0
We add all the numbers together, and all the variables
-6f-(-10f-10)+10=0
We get rid of parentheses
-6f+10f+10+10=0
We add all the numbers together, and all the variables
4f+20=0
We move all terms containing f to the left, all other terms to the right
4f=-20
f=-20/4
f=-5

See similar equations:

| 2r+5(-6-8r)=5r-4r | | -1=7b-5-8b | | P=5m^2+12m+2 | | -9x+8=-8x+6 | | 4(5x−3)=3(2x+1) | | (c/4)+5=6 | | 20+(y-10)= | | 4r-2-4=14 | | 20=1-8x+3 | | z/–4+13=17 | | -4=4+6v-5v | | 2b^2=5b+12 | | -2-33/b=12 | | 4x+5+8x+30=180 | | (6x+8)+(4x+13)+(11x+12)=x | | (6x+8)=(4x+13)+(11x+12)=x | | 12x+5+30=180 | | (100+w)(150+w)=2(100)(150) | | Q+10=n25 | | -2x-9=9+x | | (6x+8)=(4x+13)+(11x+12) | | 93=2g—27 | | (6x+8)=(4x+13)+(11x+12)+x | | -3x^2-36x=300 | | 9(x-2)=7x-5 | | 4z+8=40* | | 3u—-3=15 | | -8=5v+3+6v | | -6x+9=-x-1 | | x-22+x-6+90=180 | | 3y2y=9 | | 9(11-k)=3(3k+-3) |

Equations solver categories